Summer on the bluffs eaudiobook A novel. - Hostin, Sunny (Summer Beach, 2021)
New York Times Bestseller! The View cohost and New York Times bestselling author Sunny Hostin dazzles with this brilliant novel about a life-changing summer along the beaches of Martha's Vineyard. Welcome to Oak Bluffs, the most exclusive Black beach community in the country. Known for its gingerbread Victorian-style houses and modern architectural marvels, this picturesque town hugging the sea is a mecca for the crème de la crème of Black society—where Michelle and Barack Obama vacation and Meghan Markle has shopped for a house for her mom. Black people have lived in this pretty slip of the Vineyard since the 1600s and began buying property in the 1800s, making this posh town the embodiment of "old money." Thirty years ago, Amelia Vaux Tanner and her husband built a house high on the bluffs, a cottage they named Chateau Laveau. For decades, "Ama" played host to American presidents, Wall Street titans, and cultural icons. But her favorite guests have always been her three "goddaughters:" Esperanza "Perry" Soto, a beautiful, talented Afro-Latina lawyer with Ama's strong, yet guarded personality; Olivia Jones, a gifted Wall Street analyst with Ama's brilliant, logical mind; and Billie Hayden, a gifted marine biologist and rule-breaker with Ama's courageous free spirit. Growing up, these three goddaughters from different backgrounds came together each summer at Chateau Laveau. As adults, the cottage is a place this trio of successful yet very different women go to escape, to slow down from their hectic lives, share private time with Ama, and enjoy the gorgeous weather, cool water, and stunning views Oak Bluffs offers. This summer on the Bluffs, however, will be different. An era is ending: Ama, now nearing seventy-one, is moving to the south of France to reunite with her college sweetheart. She has invited Perry, Olivia, and Billie to spend one last golden summer together with her the way they did when they were kids. And when fall comes, she is going to give the house to one of them. Each of the women wants the house desperately. Each is grappling with a secret she fears will hurt her and her chances. By the end of summer, old ties will fray, new bonds will be created, and these three found sisters will discover they aren't the only ones with something to hide. Ama has a few secrets of her own. What she has to give them is far more than property. Between Memorial Day and Labor Day, she will tell these surrogate daughters she fiercely loves and protects everything they never knew they needed to know.